2006
DOI: 10.1086/505152
|View full text |Cite
|
Sign up to set email alerts
|

Common Polymorphisms of Toll‐Like Receptors 4 and 9 Are Associated with the Clinical Manifestation of Malaria during Pregnancy

Abstract: Toll-like receptors (TLRs) are involved in recognition of and response to Plasmodium falciparum. In 304 primiparous Ghanaian women, we examined whether common TLR4 and TLR9 polymorphisms influence susceptibility to and manifestation of malaria during pregnancy. The TLR variants did not affect P. falciparum prevalence or parasite density. However, in P. falciparum-infected women, both the TLR4 Asp299Gly and the TLR9 T-1486C polymorphisms increased the risk of low birth weight in term infants 6-fold, and, additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 14 publications
4
95
4
1
Order By: Relevance
“…Although some studies have reported no association between T-1486C and malaria susceptibility or severity 7,20,22,24,27,30 , we observed that the -1486C allele was a risk factor for severe malaria and high parasite load, which is in line with previous findings 21,24 . Moreover, -1486C has been associated with an increased risk of low birth weight in term infants born to P. falciparum-infected pregnant women 25 .Consistent with these findings, the meta-analysis of the T-1486C variant revealed a significant association with SM under the allele contrast (T vs. C) and homozygous (TT vs. CC) genetic models. Despite the fact that the stratified analysis did not detect a statistically significant association in Indian adults, its association in African children, both in T vs. C and TT vs. CC models, suggests that the findings are robust, at least in children.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Although some studies have reported no association between T-1486C and malaria susceptibility or severity 7,20,22,24,27,30 , we observed that the -1486C allele was a risk factor for severe malaria and high parasite load, which is in line with previous findings 21,24 . Moreover, -1486C has been associated with an increased risk of low birth weight in term infants born to P. falciparum-infected pregnant women 25 .Consistent with these findings, the meta-analysis of the T-1486C variant revealed a significant association with SM under the allele contrast (T vs. C) and homozygous (TT vs. CC) genetic models. Despite the fact that the stratified analysis did not detect a statistically significant association in Indian adults, its association in African children, both in T vs. C and TT vs. CC models, suggests that the findings are robust, at least in children.…”
supporting
confidence: 61%
“…Our meta-analysis results for the TLR4D299G variant were consistent with those of previous studies on diverse ethnicities from different malarial endemic regions 2,20,22 , with no difference in the genotype or allele frequency distributions of the D299G polymorphism between UM and SM subjects. Although the contribution of the 299G minor allele has been controversial in children 7,20,22,23 , adult studies show no association 2,21,24 with the exception of maternal anemia in pregnant women 25 . This could be due to a lack of adequate studies, ethnic differences, or the fact that the effect of 299G may vary with age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TLR9 signaling plays a protective role in the development of autoimmunity by modulating Treg activity in autoimmune-prone MRL mice (45). Furthermore, common polymorphisms of TLR9 are reported to be associated with the clinical manifestation of malaria during pregnancy (46). It is quite possible that malaria parasites cleverly exploit this machinery by providing a large amount of TLR9 stimulant.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, TLR4 Asp299 Gly was associated with an increased risk of maternal anemia, and TLR4 Asp299 Gly and the C allele at TLR9 −1486 were associated with subsequent infant lowbirth weight in pregnant Ghanaian women with malaria. 22 In the second, the risk of severe malaria in Ghanaian children was increased 1.5-fold and 2.6-fold with TLR4 Asp299 Gly and TLR4 Thr399 Ile , respectively. 23 Another study by Campino and others, 24 based in The Gambia and Malawi, studied the effect of TLR9 genetic variation on severe malaria.…”
Section: Introductionmentioning
confidence: 98%